Islamic Social Banking Platform (Case of Resalat Islamic Bank) - Seyed Hossein Mirjalili; Hassan Baan; Abouzar Soroosh; Mohammad Hashem Botshekan (Journal of Money and Economy, 2020)
In this paper, we examined an effective business model for the ecosystem of Islamic FinTech for Resalat Islamic Bank. The article discussed three phases of Resalat Bank development as a Platform in formulating social business models that require new value propositions, value constellations, and profit equations, and as such, resembles business model innovation. The result of the qualitative method for comparing Resalat Bank and Grameen Bank indicated that the business model of Resalat Bank is more efficient than Grameen Bank. We also discussed the challenges of transformation from the "current Islamic banking business model" to "Islamic banking as a platform" and proposes a framework for "Islamic bank as a platform" at the macro and micro levels.
Keywords: D02; G10; O16; 330; Islamic Social Banking; Platform; Business Model; Sharing Economy; Fintech